Bacterial and Yeast AAA + Disaggregases ClpB and Hsp104 Operate through Conserved Mechanism Involving Cooperation with Hsp70. Issue 21 (23rd October 2016) - Kummer, Eva; Szlachcic, Anna; Franke, Kamila B.; Ungelenk, Sophia; Bukau, Bernd; Mogk, Axel
Abstract: Escherichia coli ClpB and Saccharomyces cerevisiae Hsp104 are members of the Hsp100 family of ring-forming hexameric AAA + chaperones that promote the solubilization of aggregated proteins and the propagation of prions. ClpB and Hsp104 cooperate with cognate Hsp70 chaperones for substrate targeting and activation of ATPase and substrate threading, achieved by transient Hsp70 binding to the repressing ClpB/Hsp104 M-domain. Fundamental differences in ATPase regulation and disaggregation mechanisms have been reported; however, these differences are raising doubts regarding the working principle of this AAA + chaperone. In particular, unique functional plasticity was suggested to specifically enable Hsp104 to circumvent Hsp70 requirement for derepression in protein disaggregation and prion propagation. We show here that both ClpB and Hsp104 cooperation with Hsp70 is crucial for efficient protein disaggregation and, in contrast to earlier claims, cannot be circumvented by activating M-domain mutations. Activation of ClpB and Hsp104 requires two signals, relief of M-domain repression and substrate binding, leading to increased ATPase subunit coupling. These data demonstrate that ClpB and Hsp104 operate by the same basic mechanism, underscore a dominant function of Hsp70 in regulating ClpB/Hsp104 activity, and explain a plethora of in vivo studies showing a crucial function of Hsp70 in proteostasis and prion propagation. Graphical Abstract: Highlights: Disaggregases Hsp104/ClpB were reported to operate at different mechanisms. Both Hsp104 and ClpB rely on Hsp70 cooperation. Initial Hsp70 activity is not bypassed by activated Hsp104 or ClpB mutants. Hsp104 and ClpB activation involves increased ATPase subunit coupling. Hsp104/ClpB activation requires M-domain repression and substrate binding.